Dental Students’ Self-Perception: Health and Academics During COVID-19 Quarantine - Frias, Emilio (2021)
The aim of this study was to analyze the self-perceived general health, oral care, stress, academic environment, and harmful habits of Mexican dental students during the COVID-19 quarantine period.  This descriptive observational study consisted of a self-perception survey that was sent to dental students undergoing virtual classes. Five sections were analyzed: General Health, Oral Health, Stress, Academic Environment and Habits. For each question, students were asked to rate their perception prior to, and during the contingency, which allowed a comparison to be made between both times for each inquiry. The answers were collected into Microsoft Excel and the statistical analyses were performed using SPSS v.20. A statistically significant difference was observed between the academic years for the variables: “physical exercise” prior to quarantine, “emotional problems” and “work-load” during quarantine, and “academic efficiency” for both times. A trend towards unfavorable perception in relation to general health, academic environment, and harmful habits was observed among dental students during social isolation derived from the pandemic. It is notable that 1st-year students presented a greater impact on all the variables of interest.